Integrating programming with beaglebone black for undergraduate's "programming for engineers" syllabus - Radzi N.A.M.; Ismail A.; Karunanithi S.; Weng L.Y.; Jern K.P.; Hock G.C.; Jamaluddin J.E.; Krishnan P.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming languages; Education; Engineering; Engineering education; Engineers; Integration; Students; Bachelor degree; Beaglebone black; C programming; Undergraduate; Undergraduate students; C (programming language)